PERFORMANCE OF WASTEWATER TREATMENT PLANT (WWTP) PHYTOREMIDIATION WATER HYACINTH IN TREATING TOFU WASTEWATER - Imam Santosa; Enro Sujito; Daria Br Br Ginting (Jurnal Scientia, 2023)
Tiyuh Kibang Hamlet, Budi Jaya Village, Lambu Kibang District, Tulang Bawang Barat District, Lampung, the community has many tofu industries. Still, based on data from the Kibang Budi Jaya Health Center, diarrheal disease is one of the environmental-based diseases that still exists. Diarrheal disease is possibly one of the causes of groundwater contamination due to tofu wastewater. Currently, a prototype of the water hyacinth phytoremediation wastewater treatment plant (WWTP) has been built in Tiyuh Kibang Hamlet, which does not require expensive physical buildings and can be reached by small tofu industrial communities. The WWTP building consists of an Anaerobic Tub, a Water Hyacinth Phytoremediation Tub and a Fish Pond. This study's purpose was to analyse the Water Hyacinth Remediation Fito WWTP performance with parameters BOD, COD, TSS and pH. The methodology of this research is to check the quality of wastewater before processing (Pre Test) and after processing (Post Test) by examining the parameters of BOD, COD, TSS and pH. The results of the research are as follows: 1) The average wastewater quality before WWTP treatment parameters BOD, COD, TSS and pH are 1878.1 mg/l, 2683.4 mg/l, 3000 mg/l, 2) Wastewater quality the average after processing the Water Hyacinth Phytoremediation WWTP parameters BOD, COD, TSS and pH were 61 mg/l, 113 mg/l, 131 mg/l.